Perancangan Suspensi Depan Prototipe Campagna T-Rex Car - Febrian Febrian; Nazaruddin Nazaruddin; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In designing a safe car while driving, there are many factors to watch out for, such as the suspension system design. In this research, the design of suspension is limited only to discuss the vehicle front suspension. The suspension design process starts from the selection of suspension type, followed by kinematic simulation using Suspension Analyzer v-2.4 software, and stress analysis simulation using Autodesk Inventor software when the vehicle is in braking and turning condition. The result of kinematic simulation of front suspension using Suspension Analyzer v-2.4 was found the change of camber wheel angle by -0.38o when maximum bump (30 mm) and 0.22o when maximum rebound (-30 mm). And the results of static analysis of front suspension components using Autodesk Inventor obtained minimum safety factor value of 1.96 in braking conditions and 1.58 in turn conditions. It was concluded that the front suspension system was still within safe limits.Keyword : suspension, static analysis, kinematic analysis, safety factor